Review on the numerical investigations into the design and development of Savonius wind rotors - Roy, Sukanta; Saha, U. (Pergamon Press, 2013)
In recent era, research and development activities in the field of renewable energy, especially wind and solar, have been considerably increased, due to the worldwide energy crisis and high global emission. However, the available technical designs are not yet adequate to develop a reliable distributed wind energy converter for low wind speed conditions. The Savonius rotor appears to be particularly promising for such conditions, but suffers from a low efficiency. Till now, a number of experimentations have been carried out in the area of Savonius rotor to increase its efficiency. These large-scale experimentations involve massive costs and hazards. In this context, computational studies have shown a significant importance to carry out the research with large number of physical designs and parameters. Over the past four decades, investigations have been carried out with various computational methodologies and turbulence models to optimize the different parameters and hence the efficiency of these rotors. In the present paper, a detailed review of various computational methods addressing the influence of various operating parameters and augmentation techniques has been reported. From this review study, it is observed that with the selection of a proper computational methodology, the design, performance, and efficiency of a Savonius rotor can be enhanced significantly. © 2013 Elsevier Ltd.